PKMS “SADAR WISATA DAN SAPTA PESONA PADA MASYARAKAT DESA PANTAI INDUK GERUNG LOMBOK BARAT“ - Sri Susanty; Ander Sriwi; Murianto, Murianto; Lalu Mahsar (Media Bina Ilmiah, 2024)
Community service programs on the promotion of Tourism Consciousness and ‘Sapta Pesona’ to the Pantai Induk Gerung West Lombok need to be carried out based on preliminary observations of the Mataram Tourism College community service team. Previously, this beach was a favorite tourist spot which was always busy with many tourists because it has a beach with beautiful natural views. but now, the beach is very quiet because of high coastal erosion and a dirty environment. Pokdarwis find it difficult to disseminate information to the public about tourism awareness programs and implement sapta pesona. The program is implemented using a lecture and discussion approach and problem mapping. This event, which was attended by 25 participants, looked enthusiastic during the counseling and problem mapping. This socialization program is very important for Pokdarwis and the local community as a basis for understanding tourism, so that it can foster high motivation and participation in tourism development at Pantai Induk.